SECTOR: Source-selective and Emission-adjusted GHG Calculator for Cropland - Wassmann, Reiner; Pasco, Richard; Zerrudo, Jefferson; Bach Thi Vo, Thuong (International Rice Research Institute, 2019)
SECTOR is a Greenhouse Gas (GHG) Calculator for cropland based on the IPCC Tier 2 approach. This tool is presently available in EXCEL and – as other GHG Calculators -- requires inputs from the user on crop areas, yields and management. SECTOR has been developed in response to increasing interest in mitigation studies in cropland, in particular rice production. The tool offers a high range of flexibility in terms of sourcing emission and activity data as well as selecting a range of scales for aggregation. Moreover, SECTOR provides a streamlined framework for accelerated data input that will facilitate rapid assessments of multiple scenarios for domains with many spatial units. [Excerpt from the SECTOR User Manual]